2008
DOI: 10.1007/s00394-008-0760-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a maternal “junk food” diet during pregnancy and lactation can reduce muscle force in offspring

Abstract: Maternal malnutrition can influence muscle force production in offspring which may affect an individual's ability to exercise and thereby combat obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 15 publications
2
46
0
2
Order By: Relevance
“…17 The maximal twitch tension and maximal tetanic tension of the semitendinosus are reduced in offspring of junk food-fed mothers. 29 When expressed relative to muscle mass, force production is decreased in the offspring of junk food-fed rats, regardless of weaning diet. Taken together, these results suggest that offspring of high fat fed/obese mothers have reduced muscle mass, and the muscle they do have are weaker than offspring of control-fed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…17 The maximal twitch tension and maximal tetanic tension of the semitendinosus are reduced in offspring of junk food-fed mothers. 29 When expressed relative to muscle mass, force production is decreased in the offspring of junk food-fed rats, regardless of weaning diet. Taken together, these results suggest that offspring of high fat fed/obese mothers have reduced muscle mass, and the muscle they do have are weaker than offspring of control-fed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The primary function of skeletal muscle is contraction-induced force production for movement. Bayol et al 65 showed that the maximal twitch tension and maximal tetanic tension of the semitendinosus were reduced in 10-week-old offspring of junk food fed mothers. This reduced muscle function was observed in offspring that were exposed to the junk food diet throughout gestation, lactation and post-weaning development, as well as offspring exposed to junk food diet during gestation and lactation only.…”
Section: Evidence For Reduced Energy Expenditure In the Offspring Of mentioning
confidence: 99%
“…Activation of this pathway has been reported in inflammatory-related states of muscle atrophy and more recently in obesity-associated diseases (3). While there is some evidence regarding the impact of maternal HF diets on offspring skeletal muscle impairment (5,6,26,39), the role of intramuscular inflammation and associated catabolic pathways has not been comprehensively assessed.…”
mentioning
confidence: 99%